Metaphors regarding the concept of e-sports produced by university students in Turkey = Metafory związane z e-sportem zaproponowane przez studentów w Turcji - Kartal, Mehmet; Temel, Cenk (Zielona Góra: Lubuskie Towarzystwo Naukowe)
E-sport is developing rapidly both in the world and in Turkey, especially with increasing interest among young people. In parallel with this interest, "E-sports Student Communities" are being established at many universities in Turkey and new ones are being added to these communities every day. In this context, the aim of this research is to reveal the perceptions that university students have about the concept of e-sports through metaphors. A total of 223 students participated in the research voluntarily. The research?s sample group consists of 190 volunteer university students, 77 of were female and 113 were male, who study at different universities in Turkey in the 2020-2021 academic year.
Keywords: Turkey; e-sports; metaphor; perception; university; students; Turcja; e-sport; metafora; percepcja; uniwersytet; studenci